Comparative Analysis of Typical Meteorological Years for Poland, Determined on the Basis of Source Data from 2001-2020 - Narowski, Piotr (Instal, 2022)
The article presents the results of a comparative analysis of two climatic parameters of new typical meteorological years for Poland, calculated on the basis of the available meteorological data of the synoptic stations of the Institute of Meteorology and Water Management (IMGiW) based on source data from 1971-2000 for selected six synoptic stations. Typical meteorological years used to date in Poland in energy analyzes of buildings were developed in 2004 based on meteorological data of the IMGiW for the years 1971 – 2000. The source data used at that time included several basic 3-hour meteorological parameters and modeled values of solar radiation intensity from an indescribable mathematical model. The values in typical meteorological years developed in 2004 were criticized, particularly the values of solar irradiation. The availability of new meteorological and climatic data sets and critical comments on the data set of typical meteorological years for the area of Poland designated for 18 years meant that these data should be considered out of date. The article describes new typical meteorological years for Poland – TLM2000, for which a comparative analysis was performed with the data determined in 2004, marked as TLM1970.
Keywords: climate data; building energy simulations; meteorologic synoptic data; ERA5 reanalysis